The Abundance and Distribution of Anchovy Engraulis encrasicolus (Linnaeus, 1758) Eggs and Larvae in Izmir Bay (Central Aegean Sea) - Burcu Taylan; Belgin Hoşsucu (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the abundance and distribution of anchovy Engraulis encrasicolus (Linnaeus, 1758) eggs and larvae in İzmir Bay were examined in 2013. For this aim, seasonally obtained the plankton samples from 11 stations identified in the bay. Anchovy eggs and larvae were obtained all seasons except winter. As a result, total 6889 eggs/m², 3231 larvae/m² were obtained. The minimum and maximum diameters of anchovy eggs; in short exis 0.49 to 0.56 mm (average 0.51±0.43), in long axist 1.09 to 1.30 mm (average 1.21±0.006). Minimum and maximum larvae length is 2.28-9.8 mm.